2020
DOI: 10.1038/s41598-020-78903-0
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin protects rat hippocampal neurons against pseudorabies virus by regulating the BDNF/TrkB pathway

Abstract: Pseudorabies virus (PRV) infection can elicit nervous system disorders. Curcumin has been reported to have neuroprotective effects. However, whether curcumin can protect neurons against PRV infection and the underlying mechanisms remain unclear. In the present study, for the first time, the protective effects of curcumin against PRV-induced oxidative stress, apoptosis, and mitochondrial dysfunction in rat hippocampal neurons and the brain-derived neurotrophic factor (BDNF)/tropomyosin-related kinase B (TrkB) p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 38 publications
(28 reference statements)
0
13
0
Order By: Relevance
“…In the development of neuronal, BDNF, as an important nerve growth factors, plays an important role in the growth, survival, and differentiation of neurons [ 32 ]. BDNF enhances neuronal survival and protects synaptic function by binding to tropomyosin receptor kinase B (TrkB) [ 33 , 34 ]. Simultaneously, BDNF promotes neuronal outward growth and recombination of dendritic spines, thereby improving neuronal connectivity [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the development of neuronal, BDNF, as an important nerve growth factors, plays an important role in the growth, survival, and differentiation of neurons [ 32 ]. BDNF enhances neuronal survival and protects synaptic function by binding to tropomyosin receptor kinase B (TrkB) [ 33 , 34 ]. Simultaneously, BDNF promotes neuronal outward growth and recombination of dendritic spines, thereby improving neuronal connectivity [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Masi et al [15] have also shown that HPA caused the brain (particularly the hippocampus) to be exposed to corticosteroids, affecting neurobehavioral functions with an impairment of the AHN and that might be a major factor in the pathophysiology of depression. Additionally, many studies have indicated that the decreased expression of hippocampal BDNF and TrkB also inhibited AHN [39,40]. It was therefore speculated that the decrease in hippocampal DCX expression after SCI may have been caused by downregulation of BDNF and TrkB beginning on day seven after SCI, which might simultaneously contribute to the development of depressive-like behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…It is commonly used as a natural coloring agent and as a natural food additive (spice) ( González-Salazar et al, 2011 ). Curcumin has been reported to exert antioxidant, chemo-preventive, and neuroprotective effects ( Yang et al, 2020 ). In recent years, increasing efforts have been engaged to reveal the pharmacological mechanisms underlying the neuroprotective effects of curcumin.…”
Section: Plant-derived Medicines Limiting Platinum-induced Peripheral Neurotoxicitymentioning
confidence: 99%